The Father's Success and the Son's Failure: Explaining the Growth of Lebanon's Resistance to Syria's Invisible Occupation. (17th October 2016) - Yahel, Ido; Honig, Or
Abstract: In the 15‐year period since the Syrian military entry into Lebanon on June 1, 1976, allegedly to put an end to the civil war that broke out there a year earlier, Syria firmly solidified its control of the country, as evidenced by the signing of the "Treaty of Brotherhood, Cooperation and Coordination between Syria and Lebanon, " on May 22, 1991, which granted Syria a special status. Yet, 14 years later, on April 24, 2005, the Syrian forces withdrew from Lebanon. This article seeks to explain this relatively rapid decline in Syria's standing in Lebanon by examining the strategies of the two Syrian rulers who indirectly controlled this country during those years. It examines what was right in Hafiz al‐Asad's strategy in Lebanon, and what did not work in Bashar's policy. In 2000, the year of Hafiz al‐Asad's death, Syria's status in Lebanon seemed unshakable: 1) Lebanon's president (Emile Lahoud) acted as Damascus's puppet; 2) Hezbollah, the Shi'a militia Hezbollah largely accepted Syria's authority while it simultaneously tightened its control over southern Lebanon and also began gaining popularity in the rest of the country; and 3) finally the politics of the noble families, which had characterized Lebanon since its establishment, began to gradually give way to a politics where a political figure is measured by the level of his connections to the country's power base in Damascus. Yet, merely five years later, Syria was under immense pressure to withdraw its forces from Lebanon. This suggests that we must look at the difference between the strategies of Hafiz al‐Asad and his son Bashar for controlling Lebanon to better understand the rapid deterioration in Syria's standing in the country. We argue that the difference in the degree of anti‐Syrian pressures from Lebanon's society and political elements between the two tenures is largely rooted in the different strategies that the two Syrian presidents adopted for informally ruling Lebanon. We identify three main areas where Bashar al‐Asad made mistakes due to his failure to continue his father's methods. First, Bashar put all his cards on Hezbollah, thus antagonizing all the other groups which resented that Shi'a dominance. Second, in stark contrast to his father, Bashar distanced himself from the regular management of Lebanon's ethnic politics. Hafiz al‐Asad made sure that all the leaders of the different ethnic groups would visit Damascus and update him on their inter‐ethnic conflicts, and then he would be the one who would either arbitrate between them or, for expediency reasons, exacerbate these feuds. Once the ethnic leaders had to manage without Damascus, they learned to get along, making him far less indispensable for the running of the country. Finally, Bashar, unlike his father, did not make a real effort to gain international and regional legitimacy (or at least de‐facto acceptance) for Syria's continued control over Lebanon. Most conspicuously, while Hafiz participated in the First Gulf War against Iraq, his son supported Sunni rebels who fought against the United States‐led coalition forces there. This foreign acquiescence was significant since the Lebanese felt they had a backing when they demanded Syria's withdrawal in 2005. These different strategic approaches of the two rulers meant that the father's policies wisely laid the ground for some of the most controversial measures which were needed as part of any attempt to monopolize control over another country, such as Lebanon (assassinating popular but too independent‐minded Lebanese presidents/prime ministers or extending tenures of loyalist ones), whereas the son's policies myopically failed to do so properly. Indeed, the article will show that while both the father and the son took these same controversial measures, the responses of the Lebanese were completely different. Admittedly, some historical developments increased the Lebanese propensity to rise up against Syria, and these meant that Bashar did in fact face a harder task than his father in maintaining Syria's informal occupation. The Israeli withdrawal from its so‐called "security zone" in south Lebanon meant that one justification for the Syrian presence was gone. More importantly, the risk of renewed eruption of the civil war (which in turn had meant for many years a greater willingness by the locals to tolerate the Syrian presence which prevented the war's resumption) declined significantly due to a variety of processes that could not have been halted even with better "management" of the interethnic strife from Damascus (i.e., making sure that the ethnic groups remained in deep conflict with each other). Nevertheless, as we will show, Bashar's mistakes played a crucial role in bringing the rival ethnic groups together by making Damascus their joint enemy.